Rainforest - Chessen, Betsey (New York : Scholastic, 1998)
Photographs and simple text explore the natural environment of the Amazon rainforest.
"Scholastic early childhood"--Includes index
Keywords: Rain forest plants -- Juvenile literature; Rain forests -- Juvenile literature